2010
DOI: 10.1007/s10439-010-9995-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Effects of Coil Packing Density on Cerebral Aneurysm Fluid Dynamics: An In Vitro Steady Flow Study

Abstract: Over the past 15 years, coil embolization has emerged as an effective treatment option for cerebral aneurysms that is far less invasive than the long-standing convention of surgical clipping. However, aneurysm recurrence after coil embolization is not uncommon: recurrence rates as high as 50% have been reported in the literature. One factor that may contribute to recurrence after coiling is residual flow into the aneurysmal sac. At present, there is limited quantitative knowledge of the relationship between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 28 publications
(33 reference statements)
2
23
0
Order By: Relevance
“…Our study also reports significant changes, one example of which is that stents, in some cases, reduced aneurysmal inflow by margins comparable to those reported for embolic coils (Babiker et al, 2010). In addition, our study demonstrates that stent configuration has a significant influence on aneurysmal fluid dynamics.…”
Section: Differences In Aneurysmal Fluid Dynamics Among Stent Configusupporting
confidence: 67%
See 1 more Smart Citation
“…Our study also reports significant changes, one example of which is that stents, in some cases, reduced aneurysmal inflow by margins comparable to those reported for embolic coils (Babiker et al, 2010). In addition, our study demonstrates that stent configuration has a significant influence on aneurysmal fluid dynamics.…”
Section: Differences In Aneurysmal Fluid Dynamics Among Stent Configusupporting
confidence: 67%
“…A lost-core Sylgard s model of an idealized wide-neck basilar tip aneurysm was constructed using a process previously reported by our group (Babiker et al, 2010). The model, shown later in Fig.…”
Section: Flow Loopmentioning
confidence: 99%
“…Therefore, the conventionally recommended VER of 20-25 % can be roughly interpreted as 15.5-19.4 % when the volume is digitally measured using 3D-RA, and a VER of 20 % was set as the minimum requirement in our practice. It may be controversial to set a single VER value as a goal, because in vitro experiments and computational fluid dynamic studies have shown that a hemodynamically effective VER is dependent on neck size, lateral wall type or terminal type, and the angle made by a sac and its parent artery [1,20]. Therefore, 20 % of VER is always a minimum requirement and we aim to embolize as densely as possible.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is consistent with previous CFD-based studies and in vitro experiments. 13,15,19,20,26 Particular flow patterns were visualized due to the coil configuration (Fig 2B), which are associated with the special location of the coils at the aneurysm ostium. Specific flow characteristics also were reported by an in vivo study, in which short and disturbed streamlines were found near the aneurysm wall.…”
Section: Discussionmentioning
confidence: 99%